Answers

2014-10-18T14:04:16+08:00
Using elimination method:
3x - 5y = 9   ----equation 1
4x + 8y = 12  ----equation 2
multiply equation 1 with 4 and equation 2 with 3
(3x - 5y = 9)  x 4
12x - 20y = 36   ----equation 1'
(4x + 8y = 12)  x 3
12x + 24y = 36   ----equation 2'
subtract equation 1' from equation 2'
    12x + 24y = 36
-   12x - 20y = 36
            44y = 0
               y = 0
multiply equation 1 with 8 and equation 2 with 5
(3x - 5y = 9)  x 8
24x - 40y = 72   ----equation 3
(4x + 8y = 12)  x 5
20x + 40y = 60  ----equation 4
add equations 3 and 4
    24x - 40y = 72
+  20x + 40y = 60
    44x +0y  = 132
   44x = 132
      x = 3

1 2 1